Recombination Pattern Reanalysis of Some HIV-1 Circulating Recombination Forms Suggest the Necessity and Difficulty of Revision - Jia, Lei (Public Library of Science, 2014)
BACKGROUND: Recombination is one of the major mechanisms underlying the generation of HIV-1 variability. Currently 61 circulating recombinant forms of HIV-1 have been identified. With the development of recombination detection techniques and accumulation of HIV-1 reference stains, more accurate mosaic structures of circulating recombinant forms (CRFs), like CRF04 and CRF06, have undergone repeated analysis and upgrades. Such revisions may also be necessary for other CRFs. Unlike previous studies, whose results are based primarily on a single recombination detection program, the current study was based on multiple recombination analysis, which may have produced more impartial results. METHODS: Representative references of 3 categories of intersubtype recombinants were selected, including BC recombinants (CRF07 and CRF08), BG recombinants (CRF23 and CRF24), and BF recombinants (CRF38 and CRF44). They were reanalyzed in detail using both the jumping profile hidden Markov model and RDP3. RESULTS: The results indicate that revisions and upgrades are very necessary and the entire re-analysis suggested 2 types of revision: (i) length of inserted fragments; and (ii) number of inserted fragments. The reanalysis also indicated that determination of small regions of about 200 bases or fewer should be performed with more caution. CONCLUSION: Results indicated that the involvement of multiple recombination detection programs is very necessary. Additionally, results suggested two major challenges, one involving the difficulty of accurately determining the locations of breakpoints and the second involving identification of small regions of about 200 bases or fewer with greater caution. Both indicate the complexity of HIV-1 recombination. The resolution would depend critically on development of a recombination analysis algorithm, accumulation of HIV-1 stains, and a higher sequencing quality. With the changes in recombination pattern, phylogenetic relationships of some CRFs may also change. All these results may be critical to understand the role of recombination in a complex and dynamic HIV evolution.